RLIP76, a non-ABC transporter, and drug resistance in epilepsy - Awasthi Yogesh C; Cucullo Luca; Singhal Sharad S; Fazio Vince; Hallene Kerri L; Awasthi Sanjay; Dini Gabriele; Janigro Damir (BMC Neuroscience, 2005)
Abstract Background Permeability of the blood-brain barrier is one of the factors determining the bioavailability of therapeutic drugs and resistance to chemically different antiepileptic drugs is a consequence of decreased intracerebral accumulation. The ABC transporters, particularly P-glycoprotein, are known to play a role in antiepileptic drug extrusion, but are not by themselves sufficient to fully explain the phenomenon of drug-resistant epilepsy. Proteomic analyses of membrane protein differentially expressed in epileptic foci brain tissue revealed the frequently increased expression of RLIP76/RALBP1, a recently described non-ABC multi-specific transporter. Because of a significant overlap in substrates between P-glycoprotein and RLIP76, present studies were carried out to determine the potential role of RLIP76 in AED transport in the brain. Results RLIP76 was expressed in brain tissue, preferentially in the lumenal surface of endothelial cell membranes. The expression was most prominent in blood brain barrier tissue from excised epileptic foci. Saturable, energy-dependent, anti-gradient transport of both phenytoin and carbamazepine were demonstrated using recombinant RLIP76 reconstituted into artificial membrane liposomes. Immunotitration studies of transport activity in crude membrane vesicles prepared from whole-brain tissue endothelium showed that RLIP76 represented the dominant transport mechanism for both drugs. RLIP76-/- knockout mice exhibited dramatic toxicity upon phenytoin administration due to decreased drug extrusion mechanisms at the blood-brain barrier. Conclusion We conclude that RLIP76 is the predominant transporter of AED in the blood brain barrier, and that it may be a transporter involved in mechanisms of drug-resistant epilepsy.